(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2014)
Injuries of the maxillofacial complex represent one of the most important health problems worldwide. The incidence of maxillofacial skeleton fractures is rising globally, the main contributors being road side accidents, interpersonal violence and falls from heights. If not treated properly, such fractures may lead to life long functional and structural disability. This study was designed to determine demographics, clinical features, patterns of mandibular bone fractures, treatment and postoperative evaluation of such fractures. This was a descriptive study, based on data of 30 patients of mandible fractures, from March 2010 to February 2012. Variables examined included demographic & clinical features, patterns of mandibular bone fractures and results of open and closed reduction of isolated mandibular fractures using surgical stainless steel wire and miniplates. Patients were followed up for one year. There were 30 patients, 26 male and 4 females, age ranged from 5-70 years (mean age was 25 years). Most common causes were road traffic accident (50%), and interpersonal violence (30%).Parasymphysis (53%)and angle(20%) of mandible was most common site of mandibular fracture and Postoperative complication rate was higher in closed reduction than in open reduction cases with internal fixation (ORIF). Long-term collection of epidemiological data regarding maxillofacial skeleton and management aspects of mandibular fractures are important for the evaluation of existing preventive measures and useful in the development of new methods of injury prevention and treatment. JCMCTA 2014 ; 25 (1): 37-40